The way of the world. - CONGREVE WILLIAM (BLOOMSBURY, 1963)
The Catholic University of America, Speech and Drama Department, Rev. Gilbert V. Hartke, O.P., head, presents "The Way of the World," by William Congreve, directed by Joseph Lewis, settings and lighting by James D. Waring, costumes by Joseph F. Bella.